USE OF DRUG PATTERN IN SYMPTOMATIC ATRIOVENTRICULAR BLOCK IN CARDIAC PATIENTS AT SHAHID GANGALAL NATIONAL HEART CENTER - YAIMAN SIDDIQUE; SANJEEV GURUNG; HEMANK KC; SUNITA ADHIKARI; ANISHA KHATRI; AKASH RAI (Innovare Journal of Medical Sciences, 2024)
Objectives: Some of the medications which are used for the treatment of cardiovascular disease sometimes can impair the atrioventricular (AV) conduction, resulting in AV block. We aim to study the use of drug pattern in symptomatic AV block in cardiac patients Methods: A quantitative study method and retrospective observational research design were used; the selected study area was Shahid Gangalal National Heart Centre, Bansbari, Kathmandu. The secondary data were collected, that is, past medical records of 384 patients who were admitted to the hospital with the diagnosis of second, third, and high-degree AV block from February 2020 to July 2023. The total duration of the study was 6 months. We analyze the demographic, co-morbidities, and electrocardiography characteristics and also the use of drug pattern in AV block. The descriptive inference was used to analyze the data. Results and Discussion: Most of the patients with symptomatic AV block were from the age group above 70 years. Of 384 patients, 187 (48.7%) received calcium channel blockers (CCBs), followed by 36 (9.4%), 10 (2.6%), 5 (1.3%), and 377 (98.2%) received beta-blockers, digoxin, amiodarone, and with/without other medications, respectively, where 3.9% had drug-induced AV block which was resolved after a change in medication along with other supportive measures. Conclusion: CCBs, beta-blockers, digoxin, and amiodarone along with/without other medication are mostly used medications in patients who have AV block and AV block is rarely caused by drugs.